On the Effect of Technological Progress on Pollution: An Overlooked Distortion in Endogenous Growth - Ferreira-Lopes, A.; Sequeira, T. N.; Roseta-Palma, C. (Oxford Economic Papers, 2013)
We derive a model of endogenous growth with physical capital, human capital and technological progress through quality-ladders. We introduce welfare-decreasing pollution in the model, which can be reduced through the development of cleaner technologies. From the quantitative analysis of the model, we show clear evidence that the externality from technological progress to pollution considered in this model is sufficiently strong to induce underinvestment in R&D as an outcome of the decentralized equilibrium. An important policy implication of the main result of this article is that it reinforces the case for R&D subsidies.